Bathroom Behaviors Regarding Oral Hygiene Items During COVID-19 Home Isolation: A Cross-Sectional Study in Southern Brazil - Lopes, Ida Carolina; da Costa, Clara; Peres, Karen Glazer; Silva, Larissa Gregório; Godinho, Fernando Guimarães; Margreiter, Sissiane; Pagliari, Suelen Paravisi; Figueiredo, Daniela de Rossi (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2023)
Objective: To describe behaviors with oral hygiene items in single-bathroom households during the domiciliary isolation of individuals with positive 'Reverse transcriptase polymerase chain reaction' (RT-PCR+) in southern Brazil. Material and Methods: Cross-sectional study was conducted with Research and Monitoring Sector of COVID-19 data from Palhoça, Brazil, of individuals aged ≥18 years, living in a single-bathroom household, who had an RT-PCR positive. A link of Google Forms was used. Socio-demographic information, characteristics during the home isolation, oral hygiene, and behaviors with oral hygiene items in the bathroom were collected. Descriptive stratified analyses according to age were conducted (<40 and ≥40 years). Results: Among 524 individuals, 36% were aged ≥40 years. During isolation, according to the behaviors with oral hygiene items in the household single-bathroom, 70% (95%CI 64.9-75.5) of the youngest participants reported sharing toothbrushes in the same container and 30% (95%CI 24.4-35.1) of the oldest; use of the same toothpaste was reported by 67% (95%CI 62.8-71.7) of the youngest and 33% (95%CI 28.3-37.3) of the oldest participants. For the outcome of sharing the same toothpaste, the chances for the youngest and the oldest to share the same toothbrush container was 11 times and 6 times more, respectively. Conclusion: The individuals related good oral hygiene habits; however, behaviors with oral hygiene items in the bathroom were neglected, especially by the younger individuals.